2021
DOI: 10.3390/jcm10122586
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Serum Uromodulin and Its Association with Delayed Graft Function Following Kidney Transplantation—A Prospective Cohort Study

Abstract: Delayed graft function (DGF) following kidney transplantation is associated with increased risk of graft failure, but biomarkers to predict DGF are scarce. We evaluated serum uromodulin (sUMOD), a potential marker for tubular integrity with immunomodulatory capacities, in kidney transplant recipients and its association with DGF. We included 239 kidney transplant recipients and measured sUMOD pretransplant and on postoperative Day 1 (POD1) as independent variables. The primary outcome was DGF, defined as need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…These data are interesting as unlike other studies which have measured uromodulin in KTR [34,42 ▪ ,43], this cohort focused on the donor kidneys. To explain the higher risk of adverse kidney outcomes with higher uUMOD, the investigators demonstrated that a truncated, nonpolymerizing form of uUMOD induced major histocompatability II expression in bone marrow-derived mouse macrophages, which may have a maladaptive effect on graft function due to an immunostimulant effect [41 ▪ ]. However, given that the vast majority of uUMOD is polymerized, whether this explains the discrepant findings of this study in comparison with others is unclear.…”
Section: Role In Different Disease Statesmentioning
confidence: 58%
See 1 more Smart Citation
“…These data are interesting as unlike other studies which have measured uromodulin in KTR [34,42 ▪ ,43], this cohort focused on the donor kidneys. To explain the higher risk of adverse kidney outcomes with higher uUMOD, the investigators demonstrated that a truncated, nonpolymerizing form of uUMOD induced major histocompatability II expression in bone marrow-derived mouse macrophages, which may have a maladaptive effect on graft function due to an immunostimulant effect [41 ▪ ]. However, given that the vast majority of uUMOD is polymerized, whether this explains the discrepant findings of this study in comparison with others is unclear.…”
Section: Role In Different Disease Statesmentioning
confidence: 58%
“…Significantly, sUMOD levels 24 h after transplantation were not associated with DGF. A second larger study of 1298 KTR evaluated the association between deceased donor uUMOD with risk for all-cause graft failure and death-censored graft failure (dcGF) and DGF at 6 months post-transplantation [41 ▪ ]. In contrast to epidemiologic data in nontransplant studies, higher uUMOD levels were associated with increased risk of graft failure, dcGF, and DGF.…”
Section: Role In Different Disease Statesmentioning
confidence: 99%
“…They determined serum uromodulin pre-KT and 24 h after KT. The serum uromodulin was not higher in DGF patients (72). Recent studies regarding uromodulin are controversial; therefore, it is hard to establish its potential role in predicting the graft survival.…”
Section: Uromodulin (Umod)mentioning
confidence: 83%
“…64 Circulating UMOD has been shown to be an effective parameter for monitoring kidney function in transplant patients. Higher pretransplant circulating UMOD levels were found to be associated with lower odds for delayed graft rejection, 67 whereas in renal transplant recipients, lower circulating UMOD levels are associated with a higher risk of failure or rejection. 68,69 In recent years, the clinical value of UMOD has extended beyond being a renal pathophysiology biomarker.…”
Section: Role As a Marker Of Kidney Healthmentioning
confidence: 94%